Do Prenatal Corticosteroids Affect Brain Maturation of the Premature Infant? An Electroencephalography Study. (March 2017) - Shany, Eilon; Berger, Itai; Goldberg, Ori; Karplus, Michael; Gilat, Shlomo; Benzaquen, Oshra; Yogev, Hagai; Shalev, Ruth
Objective . To assess whether prenatal treatment with betamethasone has a significant influence on cerebral maturation indices as measured by electroencephalographic (EEG) indices. Study Design . Infants born less than 35 weeks postmenstrual age (PMA) were prospectively enrolled if their mother received a full course of bethametasone prior to delivery (study group) or not (control group); infants with major intracranial abnormalities were excluded as well as those who were sedated or needed assisted ventilation. EEG was recorded during the first 10 days of life. Interburst intervals and maximal amplitudes of theta and delta bandwidths were calculated by a signal processing software. A multivariate general linear model was used to analyze the relationship between the 2 groups and the different electrophysiologic parameters, adjusting for PMA and mode of delivery. Results . Thirty-eight infants were included in the study group and 36 in the control group. Univariate analysis demonstrated a negative correlation between PMA at test and EEG indices (interburst interval and delta and theta frequencies). Multivariate analysis demonstrated a less robust correlation of PMA and EEG indices and a positive correlation of prenatal betamethasone treatment with Theta frequencies. Repeating the data analysis separately for each study group, the above results remained significant mainly in the study group. Conclusions . Our findings suggest a possible stabilization effect of corticosteroids on the central nervous system and a possible delay of the maturation of cerebral activity related to prenatal corticosteroids use. These findings may relate to a better neurodevelopmental outcome of infants treated prenatally with corticosteroids.